THE ROLE OF PERSONAL HYGIENE IN THE PREVENTION OF INFECTIOUS DISEASES (American Journal of Research in Humanities and Social Sciences, 2026)
This paper discusses in detail the importance of personal hygiene in maintaining human health and preventing infectious diseases. Personal hygiene refers to a set of daily practices aimed at maintaining cleanliness of the body, clothing, food, and living environment. Special attention is given to the causes of infectious diseases and the main routes of transmission, including airborne, contact, foodborne, and waterborne pathways. The role of microorganisms such as bacteria, viruses, and fungi in causing diseases is also explained. Following personal hygiene rules not only protects individual health but also helps prevent the spread of infectious diseases in society. Therefore, developing a culture of hygiene is an essential factor in promoting public health and reducing disease transmission.